"General Fundamentals of Non-Olympic Sport" as a normative discipline for training of specialists in sport - Dolbysheva N.G (Kharkov National Pedagogical University, 2012)
The article presents the direction of knowledge formation in non-Olympic sport on educational competence levels 'Master' and 'Specialist' in specialty 'Sport' (according to kinds of sport). The article also exposes the structure and content of the educational subject 'Оrganizational and legal fundamentals of non-Olympic sports'. The article presents perspectives of the subject 'General Fundamentals of Non-Olympic Sport' introduction which is included in normative part of educational and professional program in amount 72 hours (2 blocks of content modules, every of which consists of two modules). Educational programme supposes 20 hours of lectures, 16 hours of seminars, 4 hours for passing modules, 32 hours for independent work. Final test is implemented in form of a credit. The subject gives the possibility to form an intelligent, theoretically competent and practically adapted to modern activity in this sphere of sport expert according to professional competences.